Research Trends in Assessment Instrument Development in Vocational High Schools: a Literature Review - Anggraini, Fitria; Oktageri, Deris; Akbar, Muhammad; Sabila, Ahda; Yuliana, Yuliana; Wakhinuddin, Wakhinuddin (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Research on evaluation instruments in Vocational High Schools (SMK) indicates a varied pattern. Nevertheless, there has been limited study and evaluation of the information provided in the research. This study seeks to examine research trends on the development of assessment instruments in SMK, based on published articles from 2019 to 2024, with a primary emphasis on the development of these instruments. The methodology employed is a literature review. This study involved a literature evaluation of 25 publications regarding developing assessment tools from various Indonesian journals, utilizing Publish or Perish and Google Scholar for data collection. The research indicated a decline in the number of studies addressing the creation of evaluation tools in vocational schools from 2019 to 2024. The R&D model is the predominant development model. Instruments for assessing knowledge are predominantly created. The creation of HOTS-based assessment tools exhibits a nearly equitable distribution. Moreover, the creation of evaluation tools predominantly lacks technological platforms.